2020
DOI: 10.1021/acs.jpcc.0c02063
|View full text |Cite
|
Sign up to set email alerts
|

Angstrom-Scale Ruler Using Single Molecule Conductance Signatures

Abstract: Experimental techniques that determine atomic arrangements in single metal–molecule–metal junctions will enable a mechanistic understanding and control of electronic properties on the nanoscale. Here, we develop a method to determine average gold and silver nanogap widths with Angstrom resolution using single molecule junction conductance and distance measurements of N,N′-diamino alkanes in a scanning tunneling microscope break junction setup. Our experiments are supported by density functional theory (DFT) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…Such 2D histograms bin the log of the conductance versus electrode displacement relative to G 0 rupture and can identify the length and binding geometry of the molecule in the junction. 26,37,46 For example, the lengths of molecular signatures in 2D histograms have been shown to scale with the length of the molecular complex binding in the junction. We compare the molecular plateau signatures measured in the presence of pySMe (N−S distance ∼4.5 Å), a heterobimetallic compound containing one axial pySMe (5b, Pt-SMe distance ∼9 Å) and a homobimetallic complex containing two pySMe linkers (6, SMe-SMe distance ∼16 Å) in 2D histograms, plotted in parts B, C, and D of Figure 3, respectively (see Figure S14 for length information).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Such 2D histograms bin the log of the conductance versus electrode displacement relative to G 0 rupture and can identify the length and binding geometry of the molecule in the junction. 26,37,46 For example, the lengths of molecular signatures in 2D histograms have been shown to scale with the length of the molecular complex binding in the junction. We compare the molecular plateau signatures measured in the presence of pySMe (N−S distance ∼4.5 Å), a heterobimetallic compound containing one axial pySMe (5b, Pt-SMe distance ∼9 Å) and a homobimetallic complex containing two pySMe linkers (6, SMe-SMe distance ∼16 Å) in 2D histograms, plotted in parts B, C, and D of Figure 3, respectively (see Figure S14 for length information).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Single-molecule electronics have the potential to enable cheap and efficient circuit fabrication at the ultimate size limit and also provide an appealing test-bed for exploring intriguing physical phenomena at the nanoscale such as quantum interference, spin filtering, , and interfacial coupling. A significant and ongoing challenge in the investigation of transport through single-molecule systems, however, is extracting meaning from the large and stochastic data sets typically produced by experimental techniques such as the scanning tunneling microscope break junction (STM-BJ) and mechanically controlled break junction (MCBJ). Both of these methods involve forming and then breaking a thin metal constriction to create a single-molecule junction in the nanogap between two metal electrodes. The primary data collected is the conductance ( G = I / V ) through the junction during the breaking process as a function of how much the two sides have been pulled apart, known as a “breaking trace”.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of this so-called “molecular yield” varies depending on the binding group strength, molecular concentration, and other unknown or uncontrolled variables. , Figure uses simulated traces to illustrate that, for short molecules whose molecular plateaus mostly overlap with the tunneling background, low molecular yield can make the molecular signature functionally impossible to identify in both the 1D and 2D histograms. Partially for this reason, most break junction experiments focus on systems with molecular yields >10%, ,,,,, and often approaching 100%, ,, because this produces histograms with clear molecular features. However, high molecular yields increase the risk of measuring multi-molecule rather than the desired single-molecule features .…”
Section: Introductionmentioning
confidence: 99%
“…The electron transport properties of molecular junctions are closely related to the structures of the functional molecules, molecule–electrode interface configurations, electrode–electrode distances, and so forth. However, different electrode materials can also result in much different transport properties for the same functional molecule, which are generally attributed to different mechanisms, such as different energy band structures of the electrodes, , different molecule–electrode coupling strengths, and different molecule–electrode interface configurations. ,, Due to the excellent conductivity and prominent extensibility, gold is the most commonly used electrode material in molecule junction investigations. The conductivity of silver is higher than that of gold, so silver has also been extensively studied in molecular electronics. ,, It is found that the conductance of ethynyl-terminated molecular junctions with silver electrodes is much higher than that of the molecular junctions with gold electrodes . However, this conductance difference is obviously not due to the different conductivities between gold and silver. The preliminary calculations show that it may be attributed to the different contact configurations of the molecular junctions with different metal electrodes .…”
Section: Introductionmentioning
confidence: 99%